Новые данные об этническом составе населения Степного Подонцовья VIII - нач.Х в. - Красильников, К.И. (Степи Европы в эпоху средневековья, 2001)
The population of the Seversky Donets river steppe in the Khazarian period till recently has been attributed to the pra-Bulgarians. However, the data obtained from the latest studies of the archaeological sites of the Seversky Donets basin allow re-evaluate the ethnic situation of the steppe Saltov culture. The dwelling constructions that were found there (50 units) give good evidence of ethnic heterogeneity of the area population. Three construction types of dwellings have been found: round overland dwellings - 7 units (14 per cent), square partly dugout dwellings - 22 units (22 per cent), and rectangular partly dugouts - 14 units (28 per cent). Each construction type had its own ethnic sources and traditions. There are also 7 constructions (14 per cent) of mixed type. Traditional heating devices have even more vivid ethnic character. 156 heating devices have been cleared out in the constructions under investigation. Among them 102 units (64 per cent) belong to traditional pra-Bulgarian open hearths. 21 units (13.4 per cent) are baker' ovens (tandyrs), and 35 units (22.6 per cent) are stoves of Slavonic type. Kitchen and table pottery are abundant on the site. The most characteristic feature of the pra-Bulgarian pottery is a round-shaped trunk. But the pottery samples found in the area show convincing evidence of the Alans’, the Slaves’, and other ethnic groups influence.